The unjust distribution of urban green infrastructure is just the tip of the iceberg: A systematic review of place-based studies. Issue 126 (December 2021) - Zuniga-Teran, Adriana A.; Gerlak, Andrea K.; Elder, Alison D.; Tam, Alexander
Abstract: Many cities are turning to greening efforts to increase resilience, but such efforts often favor privileged groups, thereby resulting in injustices. In this systematic review, we analyze 71 place-based studies of green infrastructure (GI) justice in cities worldwide. We draw from environmental justice scholarship, as well as climate and water justice literature to assess the state-of-the-art knowledge of urban GI justice. We examine the way GI is researched to improve our understanding of the types of injustices that exist in GI planning, siting, and implementation, providing rich insights into why injustices exist and pathways to address GI injustice. We find that research on GI justice in cities is growing and expanding its scope in terms of both the types of justice issues analyzed, and the groups of people excluded from the benefits of GI. We find that GI injustice stems from a history of unequal investment and non-participatory decision-making processes, where the unequal distribution of GI is only the "tip of the iceberg". To address GI injustice around distribution, cities would have to offset a decades-long lack of investment and inclusivity in decision-making processes. Pathways to achieve GI justice point to assessing unbalanced power structures, directing continuous funding to community engagement programs and greening efforts, leveraging existing infrastructure through the multifunctionality of GI, and dedicating funding mechanisms for safety and maintenance. Interdisciplinary and transdisciplinary research is needed to integrate the different dimensions of GI that are tailored to the community on the ground, and to monitor progress toward justice. Highlights: The pluralistic environmental justice framework is being used more broadly by researchers over time We find a broadening understanding of GI injustice in the literature that reflects the multidimensionality of GI Recognition uncovers other forms of GI injustice and underlying factors that cause injustice Greening efforts must democratize decision-making processes and leverage the multifunctionality of GI Interdisciplinary and transdisciplinary research is needed to place justice at the core of greening initiatives